Implementation of an Outpatient HD-MTX Initiative - Sokol, Kelsey; Yuan, Kelley; Piddoubny, Maria; Sweeney, Ellen; Delengowski, Anne; Fendler, Katlin; Espinosa, Gloria; Alberto, Judith; Galanis, Patricia; Gung, Carol; Stokley, Meghan; George, Mercy; et al. (Frontiers in Oncology, 2022)
ABSTRACT Introduction: Methotrexate (MTX) is a folate antagonist is often given in high doses (≥500 mg/m2) to treat a variety of disease processes. While inpatient administration has been the norm, outpatient administration, has been shown to be safe, effective, and patient centered. Here in we describe development of an outpatient HDMTX protocol and our initial experience. Methods: All patients were to receive their first cycle of HDMTX in the hospital to ensure they tolerate it well and also to use this time to assist in training for home administration. The outpatient protocol involved continuous IV sodium bicarbonate, along with oral leucovorin and acetazolamide. Patients were required to visit the infusion center daily for labs and methotrexate levels. Clear criteria for admission were developed in the case of delayed clearance or methotrexate toxicity. Results: Two patients completed the safety run-in phase. Both patients tolerated treatment well. There were no associated toxicity. Methotrexate cleared within 3 days for all cycles. Both patients were able to follow the preadmission instructions for sodium bicarbonate and acetazolamide. The patients reported adequate teaching on the protocol and were able to maintain frequency of urine dipstick checks. Conclusion: We developed and implemented an outpatient protocol for high dose methotrexate. This study largely details the development of this protocol and its initial safety evaluation. More work needs to be done to assess its feasibility on a larger number of patients who receive more cycles in the outpatient setting.